Mixed Training Methods: Effects of Combining Resisted Sprints or Plyometrics with Optimum Power Loads on Sprint and Agility Performance in Professional Soccer Players - Loturco, Irineu; Kobal, Ronaldo; Kitamura, Katia; Cal Abad, Cesar C.; Faust, Bruno; Almeida, Lucas; Pereira, Lucas A. (Frontiers in Physiology, 2017)
The aim of this study was to compare the effects of two different mixed training programs (optimum power load [OPL] + resisted sprints [RS] and OPL + vertical/horizontal plyometrics [PL]) on neuromuscular performance of elite soccer players during a short-term training preseason. Eighteen male professional soccer players took part in this study. The athletes were pair-matched in two training groups: OPL + RS and OPL + PL. Unloaded and resisted sprinting speeds at 5-, 10-, 20-, and 30-m, change of direction (COD) speed, and performance in the squat jump (SJ), countermovement jump (CMJ), and horizontal jump (HJ) were assessed pre- and post- a 5-week training period. Magnitude based inference with the effect sizes were used for data analysis. A possible increase in the SJ and CMJ heights and a likely increase in the HJ distance were observed in the OPL + PL group. Meaningful improvements were observed in the COD speed test for both training groups comparing pre- and post-measures. In both unloaded and resisted sprints, meaningful decreases were observed in the sprinting times for all distances tested. This study shows that a mixed training approach which comprises exercises and workloads able to produce positive adaptations in different phases of sprinting can be a very effective strategy in professional soccer players. Moreover, the possibility of combining optimum power loads with resisted sprints and plyometrics emerges as a novel and suitable option for coaches and sport scientists, due to the applicability and efficiency of this strength-power training approach.